Perbandingan First Sound Fluency (FSF) Siswa Kelas III pada Awal dan Tengah Semester Pembelajaran Aksara Bali - Ni Luh Wayan Senja Pratiwi; I Ketut Paramarta; Ida Bagus Putra Manik Aryana (Universitas Nahdlatul Wathan Mataram, 2026)
Teaching Balinese script reading at the elementary school level faces a serious challenge in the form of students’ low phonological awareness, which is caused by the complexity of phoneme representation in the Balinese script, which differs significantly from the Latin alphabet. This challenge hinders students’ ability to accurately identify the initial sounds of words. This study aims to compare the First Sound Fluency (FSF) scores of third-grade students at the beginning and midpoint of the semester to measure the development of phonological awareness in the context of Balinese script learning. The study employs a quantitative approach with a descriptive-comparative design through a simple longitudinal measurement of 24 elementary school students selected through purposive sampling. The FSF test instrument was adapted to include 24 Balinese-script words familiar to the students and analyzed using descriptive statistics (mean, median, mode, score range) without inferential testing. The results showed an increase in the average FSF score from 33.125 to 35.333, with the minimum score rising from 26 to 31, and the maximum score from 42 to 45. These findings confirm the effectiveness of FSF as an assessment tool for early literacy development based on regional scripts.